Olfactory preference conditioning changes the reward value of reinforced and non-reinforced odors - Torquet, Nicolas; Aimé, Pascaline; Messaoudi, Belkacem; Garcia, Samuel; Ey, Elodie; Gervais, Rémi; Julliard, A. Karyn; Ravel, Nadine (Frontiers in Behavioral Neuroscience, 2014)
Olfaction is a determinant for the organization of rodent behavior. In a feeding context, rodents must quickly discriminate whether a nutrient can be ingested or whether it represents a potential danger to them. To understand the learning processes that support food choice, aversive olfactory learning and flavor appetitive learning have been extensively studied. In contrast, little is currently known about olfactory appetitive learning and its mechanisms. We designed a new paradigm to study conditioned olfactory preference in rats. After 8 days of exposure to a pair of odors (one paired with sucrose and the other with water), rats developed a strong and stable preference for the odor associated with the sucrose solution. A series of experiments were conducted to further analyze changes in reward value induced by this paradigm for both stimuli. As expected, the reward value of the reinforced odor changed positively. Interestingly, the reward value of the alternative odor decreased. This devaluation had an impact on further odor comparisons that the animal had to make. This result suggests that appetitive conditioning involving a comparison between two odors not only leads to a change in the reward value of the reinforced odor, but also induces a stable devaluation of the non-reinforced stimulus.